2023
DOI: 10.1021/acsaenm.2c00136
|View full text |Cite
|
Sign up to set email alerts
|

Aminosilane-Modified Ordered Hierarchical Nanostructured Silica for Highly-Selective Carbon Dioxide Capture at Low Pressure

Abstract: Ordered hierarchical nanostructured silica (OHNS) adsorbents were prepared, and their surface was controllably modified by aminosilanization using two different aminosilanes, one bearing one primary amine unit per molecule (4-aminobutyltriethoxysilane, ABTS) and the other bearing both a primary and a secondary amine (N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, AAMS). Following physicochemical, structural, morphological, and porosity characterization, the CO2 adsorption performance was evaluated at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…Functionalized amine sorbents are widely recognized for their selectivity for CO 2 over N 2 and O 2 in numerous publications. 33,84,85…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized amine sorbents are widely recognized for their selectivity for CO 2 over N 2 and O 2 in numerous publications. 33,84,85…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized amine sorbents are widely recognized for their selectivity for CO 2 over N 2 and O 2 in numerous publications. 33,84,85 While oxygen is a signicant component of the air, our equipment did not allow us to study the selectivity of the sorbents for oxygen. However, a study by Belmabkhout et al 59 demonstrated that the adsorption of oxygen onto aminefunctionalized silica was very similar to that of nitrogen.…”
Section: Adsorption Isotherms and Selectivitymentioning
confidence: 99%
“…According to different studies in the literature, ,, there is strong evidence that most of the chemisorption of CO 2 on amines occurs at low pressures up to 5 kPa (50 mbar) for medium and high functionalization degrees. Reports simulating the chemisorption of CO 2 on amine-grafted materials have either assumed a 100% conversion rate where all amines are present as carbamate–ammonium pairs, ,, or have used experimental adsorption studies to estimate the conversion rate of the amine–CO 2 reaction into carbamate–ammonium pairs.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the CO 2 emission from fluid catalytic cracking (FCC) regenerators may contain a CO 2 concentration in the range of 20−35%. 3 Currently, natural gas (NG) is considered to be the primary source of world energy, and it is expected to grow in the future. However, the effluent streams from the well may include several impurities, which contain 4−50% CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the subject of CO 2 capture, the high CO 2 content gas effluents need significant CO 2 capture and storage (CCS) technologies to overcome the urgent power needs. 1,3 The development of efficient technologies and advanced materials for CO 2 capture and storage (CCS) has received tremendous attention during the last decides. Among the separation methods, absorption, adsorption, membrane separation, and cryogenic separation are commonly employed techniques for CO 2 removal from gas mixtures.…”
Section: Introductionmentioning
confidence: 99%